SLE non-coding genetic risk variant determines the epigenetic dysfunction of an immune cell specific enhancer that controls disease-critical microRNA expression - Hou, Guojun; Harley, Isaac T. W.; Lu, Xiaoming; Zhou, Tian; Xu, Ning; Yao, Chao; Qin, Yuting; Ouyang, Ye; Ma, Jianyang; Zhu, Xinyi; Yu, Xiang; Xu, Hong; et al. (Nature communications, 2021)
Since most variants that impact polygenic disease phenotypes localize to non-coding genomic regions, understanding the consequences of regulatory element variants will advance understanding of human disease mechanisms. Here, we report that the systemic lupus erythematosus (SLE) risk variant rs2431697 as likely causal for SLE through disruption of a regulatory element, modulating miR-146a expression. Using epigenomic analysis, genome-editing and 3D chromatin structure analysis, we show that rs2431697 tags a cell-type dependent distal enhancer specific for miR-146a that physically interacts with the miR-146a promoter. NF-kB binds the disease protective allele in a sequence-specific manner, increasing expression of this immunoregulatory microRNA. Finally, CRISPR activation-based modulation of this enhancer in the PBMCs of SLE patients attenuates type I interferon pathway activation by increasing miR-146a expression. Our work provides a strategy to define non-coding RNA functional regulatory elements using disease-associated variants and provides mechanistic links between autoimmune disease risk genetic variation and disease etiology. Enhancers shape gene expression patterns and are involved in disease pathogenesis. Here the authors demonstrate a strategy to screen functional regulatory elements for non-coding RNAs ― illustrated with miR-146a ― and link autoimmune disease risk genetic variants to autoimmune disease etiology.